Improved Learning Outcomes Shooting Football Media Audio Visual On Private Student Class V SD Titi Berdikari Terrain: Improved Learning Outcomes Shooting Football Media Audio Visual On Private Student Class V SD Titi Berdikari Terrain - Ade Evriansyah Lubis (Journal of Midwifery and Nursing, 2020)
This study aims to determine the learning outcome shooting football in the fifth grade elementary school students Titi Berdikari Terrain Private School Year 2018/2019, through the Audio Visual Media. This research is a classroom action research (PTK). The research was conducted in two cycles, with each cycle consisting of planning, action, assessment, and reflection. Sources of data in this study a test to students in the form of application of the basic techniques of football shooting. Data collected by the assessment of learning outcomes football shooting. Data analysis techniques used descriptively based on a qualitative analysis by percentage. The results obtained from the observation that 15 students declared complete (47%), while 17 other students declared incomplete (53%). In the first cycle in which 24 students obtained results declared complete (75%), while eight other students declared incomplete (25%). And the second cycle in which 27 students obtained results declared complete (85%), while 5 other students declared incomplete (15%).